High‐Speed Interferometric Scattering Tracking Microscopy of Compartmentalized Lipid Diffusion in Living Cells - Reina, Francesco; Eggeling, Christian; Lagerholm, Christoffer (Wiley, 2026)
Lateral diffusion measurements have been -used to infer information about the nano-organization of membranes. We employed interferometric scattering (ISCAT) microscopy at an acquisition rate of 2 kHz to revisit the diffusion dynamics of a phospholipid analog on the plasma membrane of Ptk2 cells. The ISCAT trajectory data are analyzed with an unbiased, statistics-driven pipeline to identify the most likely diffusion mode from a set of plausible diffusion modes. At the ensemble average level, the data are best described as transient compartmentalized diffusion with an average compartment size of 100-110 nm, transient confinement time of 8-10 ms, intracompartmental diffusion coefficient of 0.7-0.9 mu m2 s-1, and intercompartmental diffusion coefficient of 0.3-0.4 mu m2 s-1. The same analysis applied at the single-trajectory level identifies a complex variety of diffusion modes with 7-8% free, 13-14% confined, 40% transient compartmentalized, and 40% anomalous diffusion. Measurements with larger (& Oslash;40 nm) as compared to smaller (& Oslash;20 nm) gold nanoparticles are found to influence the diffusion rate and confinement strength, but not the underlying lipid diffusion modes. Using Monte Carlo simulations, these experimental results are explored in the wider context of relevant literature. This analysis paints a unifying picture of lipid diffusion on mammalian cell membranes transcending differences between experimental techniques.